Low risk of CD4 decline after immune recovery in human immunodeficiency virus-infected children with viral suppression - Pope Kosalaraksa (2018)
© The Author 2016. Background. Regular CD4 count testing is often used to monitor antiretroviral therapy efficacy. However, this practice may be redundant in children with a suppressed human immunodeficiency virus (HIV) viral load. Methods Study end points were as follows: (1) a CD4 count <200 cells/mm3followed by a CD4 count ≥200 cells/mm3(transient CD4 <200); (2) CD4 count <200 cells/mm3confirmed within 6 months (confirmed CD4 <200); and (3) a new or recurrent World Health Organization (WHO) stage 3 or 4 illness (clinical failure). Kaplan-Meier curves and Cox regression were used to evaluate rates and predictors of transient CD4 <200, confirmed CD4 <200, and clinical failure among virally suppressed children aged 5-15 years who were enrolled in the TREAT Asia Pediatric HIV Observational Database. Results Data from 967 children were included in the analysis. At the time of confirmed viral suppression, median age was 10.2 years, 50.4% of children were female, and 95.4% were perinatally infected with HIV. Median CD4 cell count was 837 cells/ mm3, and 54.8% of children were classified as having WHO stage 3 or 4 disease. In total, 18 transient CD4 <200 events, 2 confirmed CD4 <200 events, and 10 clinical failures occurred at rates of 0.73 (95% confidence interval [95% CI], 0.46-1.16), 0.08 (95% CI, 0.02-0.32), and 0.40 (95% CI, 0.22-0.75) events per 100 patient-years, respectively. CD4 <500 cells/mm3at the time of viral suppression confirmation was associated with higher rates of both CD4 outcomes. Conclusions Regular CD4 testing may be unnecessary for virally suppressed children aged 5-15 years with CD4 ≥500 cells/ mm3.